Mengulas Regulasi Mengenai Keamanan Data Pribadi Konsumen Dalam Kegiatan Jual Beli Online - Nadia Rahma Fitri; Fitri Dwi Nurmaliza; Helfira Citra (Jurnal Kajian Hukum dan Pendidikan Kewarganegaraan, 2025)
The advancement of information technology has significantly increased online buying and selling (e-commerce) activities, but it has also raised issues regarding the protection of consumers' personal data. This journal discusses the legal regulations governing the security of personal data in online transactions and the responsibilities of business actors in safeguarding such data. The research uses a normative juridical approach by analyzing various laws and regulations, including Law No. 8 of 1999 on Consumer Protection, the Electronic Information and Transactions Law (ITE Law), and Law No. 27 of 2022 on Personal Data Protection. The findings reveal that although several regulations provide rights and protection for consumers' personal data, there remains a legal gap concerning the specific responsibilities of e-commerce operators. Personal data protection in e-commerce requires transparency, clearly defined legal accountability, and standardized privacy policies. Therefore, regulatory harmonization and increased legal awareness among business actors and consumers are essential to ensure the optimal protection of consumer rights in the digital era.